DEKONSTRUKSI STIGMA PSK DALAM NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL SAADAWI - Septrian, Aryo Aji; Satvikadewi, A.A.I Prihandari; Muthmainnah, Amalia Nurul (Sintesa, 2025)
​ This research aims to identify and describe the forms of deconstructive messages of the stigma of sex workers found in the novel Women at Point Zero by Nawal El Saadawi, based on the five basic assumptions of feminist standpoint theory proposed by Nancy Hartsock. (West & Turner, 2010). The findings were then analyzed using the critical discourse analysis approach by Sara Mills, determining the subject-object and reader-writer positions. In this novel, Firdaus as the main character positions herself as the subject or narrator. As someone who occupies the position of subject, Firdaus has the opportunity to describe and narrate her perspective, experiences, and actions as a woman working as a sex worker. Firdaus's perspective, experiences, and actions represent her resistance against the system of male power dominance. Through this representation, Firdaus deconstructs the stigma surrounding sex workers, which is conveyed through quotes, sentences, and dialogues delivered by Firdaus in her role as subject or narrator. The object in this novel is men in general, and the position of the object will change according to the background of the issues narrated by Firdaus. Meanwhile, the reader's position is to understand and feel Firdaus's struggle in deconstructing the stigma of sex workers through his resistance against the dominance of male power, which is depicted through sentences and descriptions in this novel.